2023
DOI: 10.1111/jfpe.14320
|View full text |Cite
|
Sign up to set email alerts
|

Bionanocomposites for active and smart food packaging: A review on its application, safety, and health aspects

Abstract: In recent years, the concept of plastic replacement and its optimal solution has commenced in the food-packaging sector. In that line, integrating nanotechnology with food packaging to improve material properties, aligned with the concept of active and intelligent packaging, has attracted consumer and industry attention. This review outlines the basics of bionanocomposites (BNCs), processing techniques, and their corresponding functions in innovative packaging techniques. The barrier, thermal, mechanical, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 165 publications
(228 reference statements)
0
3
0
Order By: Relevance
“…The alginate-and carrageenan-based films are commonly produced by employing a solution casting approach, and it has been reported that the neat films are brittle, and physical properties (mechanical, barrier, and hydrophobicity) are relatively weak for food packaging purposes (Roy & Rhim, 2020d;Santos et al, 2022a;Wang et al, 2023). Therefore, to enhance the physical and functional performances of both films, usually plasticizers, other polymers, crosslinkers, and bioactive functional ingredients (nanofillers, plant extract, bioactive compounds, natural colorant, and EOs) are usually added into the film-forming formulation (Bose et al, 2023;Fadiji et al, 2023;Ghosh et al, 2023;Kishore et al, 2023;Roy, Ezati, et al, 2023;Roy, Zhang, et al, 2023). The combination of other polymers and the addition of plasticizers and cross-linkers are highly effective to improve the packaging films' physical properties; on the flip side, the incorporation of functional additives helps to impart the antioxidant, antimicrobial activity into the film (Khan, Priyadarshi, et al, 2023;Tran et al, 2020;.…”
Section: Food Packaging Applicationsmentioning
confidence: 99%
“…The alginate-and carrageenan-based films are commonly produced by employing a solution casting approach, and it has been reported that the neat films are brittle, and physical properties (mechanical, barrier, and hydrophobicity) are relatively weak for food packaging purposes (Roy & Rhim, 2020d;Santos et al, 2022a;Wang et al, 2023). Therefore, to enhance the physical and functional performances of both films, usually plasticizers, other polymers, crosslinkers, and bioactive functional ingredients (nanofillers, plant extract, bioactive compounds, natural colorant, and EOs) are usually added into the film-forming formulation (Bose et al, 2023;Fadiji et al, 2023;Ghosh et al, 2023;Kishore et al, 2023;Roy, Ezati, et al, 2023;Roy, Zhang, et al, 2023). The combination of other polymers and the addition of plasticizers and cross-linkers are highly effective to improve the packaging films' physical properties; on the flip side, the incorporation of functional additives helps to impart the antioxidant, antimicrobial activity into the film (Khan, Priyadarshi, et al, 2023;Tran et al, 2020;.…”
Section: Food Packaging Applicationsmentioning
confidence: 99%
“…[90] and Kishore et al [91] precisely summarized the use of nanostructured materials in food packaging. Due to their increased surface-to-volume ratio and quantum-confined structures, the nanomaterials possess unique and peculiar properties.…”
Section: Nanosensorsmentioning
confidence: 99%
“…Carrageenan-based films are generally produced using solvent casting, and although the films are neat and brittle, their physical properties (mechanical, barrier, and hydrophobic) are relatively weak, so they are reported to be used for food packaging [30][31][32]. Therefore, to improve the physical and functional performance of the film, certain substances such as plasticizers, other polymers, crosslinkers, and bioactive functional ingredients (nanofillers, plant extracts, bioactive compounds, natural colorants, essential oils) are incorporated into the filmforming solution to produce favorable results [2,[33][34][35][36][37]. Combination with other substances, such as crosslinkers and plasticizers, can work synergistically to improve the physical properties of packaging films.…”
Section: Food Packaging Materials Based On Carrageenanmentioning
confidence: 99%